Policy experimentation and institutional power dynamics in China’s higher education reforms - Han, S (2017)
In response to the challenges presented by unprecedented growth in higher education (HE) since 1978, China adopted policy experimentation (PE) as a means of introducing and testing HE reforms. This study involves four in-depth case studies of important reforms facilitated by policy experiments at different junctures of China's HE development: early 1980s, mid-late 1980s, late 1990s, and early 2010s. Within each reform, two elite universities as 'experiment points' (shi dian) were selected. Through cross-case analysis informed by semi-structured interviews and extensive documentary analysis, the study offers a holistic historical perspective on how PE has been used to bring about institutional changes in China’s higher education. The study documents different rationales used for implementing policy experiments. State actors use PE to exert pressure on universities to introduce reforms, to lower associated risks and to strengthen the nation's overall HE policymaking capacity in a volatile and extremely heterogeneous context. For their part, university leaders have adopted PE locally to navigate China’s politically charged policymaking environment and to negotiate with state actors more favourable terms for reforms. Therefore, the PE approach enables state-university interactions and power negotiations that create and maintain 'strategy space' for consensus-building and institutional changes. It is an iterative process characterised by central-local interaction and intentionally ambiguous boundaries. The state, however, retains ultimate authority for legitimatising, selecting and expanding policy experiments. It is best understood as elite-enabled experimentation within existing political hierarchies. Over time, China’s PE approach has become a semi-institutionalised mechanism for HE reforms. In the various policy experiments discussed in this study, PE functions as a productive, disciplinary and symbolic force at different stages of the policy process. Sometimes it appears to offer a genuinely productive mechanism for producing, identifying and negotiating innovative policy options that may be replicated at a larger scale; sometimes its essential use lies in its generated regulative effect; and sometimes it assumes more of a symbolic role allowing the government to acquire or consolidate reform legitimacy. Policy processes are mediated by these different uses of PE towards either reform efficacy or institutional conformity. This study situates these reforms within broader political, social, economic and historical contexts, and highlights the policy implications for higher education reform internationally.